Evaluation Of Gmp And Recommendation Of Haccp At Sme Robusta Coffee In Tanggamus, Lampung - Zada Agna Talitha; Khairunisa Nurdiani; Hesti Ayuningtyas Pangastuti; Ilham Marvie; Dina Fithriyani; Syahrizal Nasution (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2021)
Coffee was a type of beverage that widely consumed and favored by Indonesians. The level of coffee consumption in Indonesia increases every year. Lampung is one of the largest coffee producing provinces in Indonesia with Tanggamus being the 2nd highest coffee-producing district in Lampung. This has led to the growth of Small and Medium Enterprise (SME) of coffee at Tanggamus area, one of which was the processing of Robusta ground coffee. These SME produced robusta coffee to be marketed throughout Indonesia and often export to customers abroad. Therefore, SME owners must maintain the quality and quality of coffee by implementing GMP (Good Manufacturing Practices). This causes the need for evaluation of GMP at SME Tanggamus ground coffee to ensure product quality and quality as well as Yeast and Mold Plate also Total Plate Count testing to determine the level of product safety. In addition, there we also gived some recommendations for the application of the HACCP system to SME. Based on the results of observations on the application of GMP at SME Robusta Tanggamus Ground Coffee, there are 12 elements that are checked according to the requirements and there are 2 elements that should have an effort to improve. The results of YMP and TPC tests on Tanggamus robusta ground coffee products showed that the product did not contain mold, yeast, and microbes. Based on the recommendations for the application of the HACCP system, regular observations of the water used for washing coffee beans are required.